AUF EINER BRÜCKE ZWISCHEN TITEL UND TEXT – TITELFUNKTIONEN - Makowska, Magdalena (Acta Neophilologica, 2010)
The present article constitutes an attempt to answer the question what functions are performed by a literary title in reference to the text preceding it and in the relation: text’s author and its recipient. At the beginning presented are general functions of a text, later on followed by an analysis of the functions of a literary title on the basis of a corpus made up of book titles within the range of women’s literature. Literary title and its functions are analyzed against the background of text linguistics and psycholinguistics.